The Taxonomy Of CSR In India - Kapoor, Anurag (2003)
This paper is an attempt to classify and understand the nature of Corporate Social Responsibility in India. Drawing on various researches I build a platform for conducting my study, where my focus is on the various types of businesses in India; Large Indian Companies, Multinationals, State Owned Enterprises, and Small-Medium Enterprises. To classify the kinds of CSR models existent in India, I embark on an exploratory research, surveying 32 companies and inquiring the major motives for indulging in CSR. This survey was further accompanied with 3 interviews of SMEs for gaining a deeper insight. On obtaining the results, using the one-way ANOVA technique, I observed the existence of basically two models of CSR; paternalistic and transnational. The existence of these models was evidence for both global and local pressures for CSR on Indian businesses. These results assist us in understanding the implications for MNCs that are already in India and those that see India as a lucrative destination in the near future, where MNCs may have to adopt a leading role in educating the new initiatives on CSR to Indian businesses.